Ion channel targeted mechanisms of anti-arrhythmic Chinese herbal medicine Xin Su Ning - Wang, T; Xie, W; Yu, J; Ellory, C; Wilkins, R; Zhu, Y-L; Ma, Y-L (Frontiers Media, 2019)
Xin Su Ning (XSN) is a China patented and certified herbal medicine used to treat premature ventricular contractions (PVCs) since 2005. A recent completed clinical trial of 861 patients showed that XSN had similar PVC inhibition rate to the class I antiarrhythmic drug mexiletine, at 65.85% for XSN and 63.10% for mexiletine. We have previously reported that XSN prolongs action potential duration (APD) and suppresses action potential amplitude (APA) of the cardiac ventricular myocytes. In this report we aim to reveal the effect of XSN on the ionic channels that govern APD and APA, which would help to explain the cellular electrophysiological mechanism of XSN. Our main findings are: (1) On ECG recorded in isolated rat, in the presence of XSN the amplitude of R wave was significantly decreased and the amplitude of T wave was increased significantly; (2) XSN blocked hNaV1.5 channel stably transfected cell line in a dose-dependent manner with an IC50 of 0.18 ± 0.02 g/L; and (3) XSN suppresses hERG channels in a dose-dependent manner with an IC50 of 0.34 ± 0.01 g/L. In conclusion, the clinical antiarrhythmic efficacy of XSN is based on its class I and Class III antiarrhythmic properties by suppression hNaV1.5 channel and hERG channels, which are directly responsible for XSN’s effect on APA suppression and APD prolongation.